Identification of a European interserotypic reassortant strain of infectious bursal disease virus. Issue 1 (2nd January 2017) - Soubies, Sébastien M.; Courtillon, Céline; Briand, François-Xavier; Queguiner-Leroux, Maryline; Courtois, David; Amelot, Michel; Grousson, Karine; Morillon, Paul; Herin, Jean-Bernard; Eterradossi, Nicolas
ABSTRACT: Infectious bursal disease virus (IBDV, family Birnaviridae ) is a bi-segmented double-stranded RNA virus for which two serotypes are described. Serotype 1 replicates in the bursa of Fabricius and causes an immunosuppressive and potentially fatal disease in young chickens. Serotype 2 is apathogenic in poultry species. Up to now, only one natural event of interserotypic reassortment has been described after the introduction of very virulent IBDV (vvIBDV) in the USA in 2009, resulting in an IBDV strain with its segment A related to vvIBDV and its segment B related to US serotype 2 strain OH. Here, we present the first European isolate illustrative of interserotypic reassortment. The reassorting isolate, named 100056, exhibits a genomic segment A typical of current European vvIBDV but a segment B close to European serotype 2 viruses, supporting an origin distinct from US strains. When inoculated into SPF chickens, isolate 100056 induced mild clinical signs in the absence of mortality but caused a severe bursal atrophy, which strongly suggests an immunosuppressive potential. These results illustrate that interserotypic reassortment is another mechanism that can create IBDV strains with a modified acute pathogenicity. As a consequence, and for a more precise inference of the possible phenotype, care should be taken that the molecular identification of IBDV strains is targeted to both genome segments.